2015
DOI: 10.1111/1753-0407.12256
|View full text |Cite
|
Sign up to set email alerts
|

Lower irisin level in patients with type 2 diabetes mellitus: A case‐control study and meta‐analysis

Abstract: This study confirmed that circulating irisin concentrations were significantly lower in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 16 publications
6
60
0
5
Order By: Relevance
“…Irisin levels on patients with T2DM and additional findings Five studies [6,12,20,21,27] of this review showed reduced levels of irisin on patients with T2DM. Other three researches [22,25,26] did not evidence significant differences between diabetic patients and control groups.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Irisin levels on patients with T2DM and additional findings Five studies [6,12,20,21,27] of this review showed reduced levels of irisin on patients with T2DM. Other three researches [22,25,26] did not evidence significant differences between diabetic patients and control groups.…”
Section: Discussionmentioning
confidence: 78%
“…Zhang et al [27] aimed on their study to stablish a confidence interval of the irisin levels on patients with T2DM, using a case-control study and a meta-analysis. In the case-control study, the irisin concentrations were lower on newly-diagnosed diabetic patients when compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations